A rare case of isolated rectal laceration during parturition: consideration of the controversial role of the episiotomy and literature review. (3rd August 2022) - Mercorio, Antonio; Della Corte, Luigi; Bifulco, Giuseppe; Giampaolino, Pierluigi
Abstract: Background: Rectal laceration without sphincter lesion during childbirth is an unusual presentation. Like all the other severe lacerations during parturition, if left undiagnosed and untreated could hesitate in serious short and long term complications. Episiotomy once considered a routine procedure in nulliparous and a safeguard against severe tissue trauma nowadays is undergoing criticism and his effectiveness reconsidered. Currently, a policy of "selective" use of episiotomy is recommended only when an impending risk of lacerations is identified. When, according to this proposal, in the absence of risk factors episiotomy is not performed and complications occur, the medicolegal implication could arise. Case: A 29-year-old primigravida was admitted with spontaneous onset of labor at 41 weeks after an uncomplicated pregnancy. During the second stage of labor a spurt of siero- hemorrhagic fluid was noted trough the anus. In absence of recognized risk factor episiotomy was not performed. A healthy 3650 grams female was born in a fair condition. Rectal examination immediately after delivery revealed a longitudinal laceration with un undamaged sphincter. The rectal tear was repaired and recovery was uneventful. Conclusions: In our as in the other cases here reviewed a severe laceration occurred unexpectedly and unpreventably in patients where, according to a selective regime, episiotomy was not performed. In this setting, if severe short and long term complications ensued, especially in nulliparous, the decision to withhold episiotomy could be a source of medicolegal issues. Therefore a detailed informed consent is necessary to offer to patients a full disclosure on the role of episiotomy, its recent indications as well as the possible complications stemming from both executing or withholding this procedure.